Pengaruh Atribut Produk, Kepercayaan Merek, Negara Asal Terhadap Niat Beli Pada Konsumen Minuman Probiotik Yakult - Ella Anastasya Sinambela; Roudhotul Nur Azizah; Utami Puji Lestari; Ernawati Ernawati; Fayola Issalillah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Nowadays people are starting to realize that they need to take care of their health before they get sick. So that consumers begin to regularly consume health drinks such as Yakult. Yakult probiotic drink has been around since 1934 and has products that are in demand by consumers. Competition with other brands makes Yakult management need to implement marketing strategies to increase consumer buying intentions. This study aims to determine the effect of product attributes, brand trust, and country of origin on consumers' purchase intentions. The research population is the Yakult Probiotic drink consumers. Researchers used 100 respondents as a sample. The analysis technique used is multiple linear regression. The results of the study indicate product attributes on consumer purchase intentions. Furthermore, brand trust has also been shown to have a significant influence on consumers' purchase intentions. Data processing also shows a significant influence by the country of origin on consumers' purchase intentions.